Judgment Considerations Policy In Decree Of The Court Criminal Statement Based On Criminal Destination - Sulistiyawan Doni Ardiyanto; Eko Soponyono Soponyono; Achmad Sulchan (Jurnal Daulat Hukum, 2020)
Crime theft is usually influenced by several factors, such as livelihoods with neatly organized networks or syndicates or some that do so due to economic pressures that force the offender to commit the crime because in his mind there is no longer a way out other than stealing. The formulation of the problem in this research is What is the judge's judgment policy in deciding cases of theft based on criminal destinations in the Draft Law of the Criminal Code, and in Act No. 48 On judicial power ?. The method of approach used is sociological juridical. This type of research is descriptive method. Source of data used from primary and secondary data. In this case the judge in providing a criminal decision must provide the benefit of the convicted person to undergo his conviction and life after leaving the prison to return to the community again. Because the provision of an unfair criminal will affect the survival of the convicted person. The purpose of punishment is as a judge's consideration in deciding the theft of criminal case which is supported by a juridical element in Article 56 of the Criminal Code Bill, and Act No.48 of 2009 On Judicial Power in Article 5 paragraph (1) and Article 8 paragraph (2).Keywords: Judge's Considerations, Theft of Crimes, Criminal Purpose.